Who was Bruce Lee? - Gigliotti, Jim; Hinderliter, John
Chronicles the life and career of well-known actor and martial arts master, Bruce Lee, from his childhood in Hong Kong to his untimely death at the age of thirty-two.
Includes bibliographical references (pages 104-105).
Keywords: Actors -- United States -- Biography -- Juvenile literature; Martial artists -- United States -- Biography -- Juvenile literature; Actors and actresses; Martial artists